2020
DOI: 10.48550/arxiv.2011.11374
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nature of $X(6900)$ and its production mechanism at LHCb

Chang Gong,
Meng-Chuan Du,
Qiang Zhao
et al.

Abstract: We show that the Pomeron exchanges play a unique role in vector charmonium scatterings. Such a mechanism can provide a natural explanation for the nontrivial structures in the di-J/ψ spectrum observed by the LHCb Collaboration. The narrow structure X(6900), as a dynamically generated resonance pole, can arise from the Pomeron exchanges and coupled-channel effects between the J/ψ-J/ψ, J/ψ-ψ(2S) scatterings. A pole structure near the di-J/ψ threshold is also found. Meanwhile, we predict that X(6900) can produce … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 52 publications
1
13
0
Order By: Relevance
“…Moreover, a broad structure ranging from 6.2 to 6.8 GeV and a hint for another structure around 7.2 GeV were also reported at the same time [33]. These exotic structures observed in LHCb immediately attracted great attention to study the fully-charm cccc tetraquarks for their mass spectra , their production mechanisms [57,[62][63][64][65][66][67][68][69][70][71] and their decay properties [37,46,[72][73][74][75][76]. Since the absence of light quarks, a fully-heavy tetraquark system is more likely to form a compact tetraquark state via the gluon-exchange color interaction, but rather than a loosely hadron molecule combined by the light meson exchanged interaction [77,78].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a broad structure ranging from 6.2 to 6.8 GeV and a hint for another structure around 7.2 GeV were also reported at the same time [33]. These exotic structures observed in LHCb immediately attracted great attention to study the fully-charm cccc tetraquarks for their mass spectra , their production mechanisms [57,[62][63][64][65][66][67][68][69][70][71] and their decay properties [37,46,[72][73][74][75][76]. Since the absence of light quarks, a fully-heavy tetraquark system is more likely to form a compact tetraquark state via the gluon-exchange color interaction, but rather than a loosely hadron molecule combined by the light meson exchanged interaction [77,78].…”
Section: Introductionmentioning
confidence: 99%
“…With the observations at LHCb, the fully-heavy tetraquark system has again attracted a lot attention from the community. Theoretical studies of various properties of such systems can be found in the literature, such as calculations of the mass spectrum , production mechanisms [56][57][58][59][60][61][62], strong decays [63,64], and analyses of the measured di-J/ψ invariant mass spectrum [65][66][67][68][69][70][71] based on different scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…In Ref. [70] it is proposed that the Pomeron exchange between two vector charmonium states can provide strong near-threshold couplings and then dynamically generate pole structures above the two vector charmonium thresholds. Other solutions include treating the narrow X(6900) as a light Higgs-like boson [73], and X(6900) and X(7200) as gluonic tetracharm states [72], or Ξcc Ξ cc molecules [74].…”
Section: Introductionmentioning
confidence: 99%
“…The X(6900) has been interpreted as P -wave fully-charmed tetraquark [2,8,16], or the radially excited S-wave tetraquark [4,6,10,12,14,16,22,23,25] or even the ground state Swave tetraquark [15]. Alternatively, the X(6900) is also suggested to be a χ c0 χ c0 or P c P c molecular state [9,24], 0 ++ hybrid [20], the resonance formed in charmonium-charmonium scattering [3,5], or the kinematic cusp arising from final-state interaction [11,13,17,19]. There has even been some attempts to tie X(6900) with some beyond Standard Model scenario [18,21].…”
Section: Introductionmentioning
confidence: 99%
“…Since then, the mass spectra and decay pattern of the fully-charmed tetraquarks (hereafter T 4c ) have been extensively investigated in various phenomenological models, such as quark potential models [2, 3, 5-7, 10, 12, 14, 15, 23, 25] and QCD sum rules [4,8,20,22,33]. The studies on T 4c production are relatively rare [7,19,[34][35][36][37][38][39][40], most of which heavily rest upon some phenomenological ansatz such as quark hadron duality and color evaporation model.…”
Section: Introductionmentioning
confidence: 99%